La producción social de la diferencia humana como fundamento antropológico de los derechos humanos negativos - Turner, Terence (Revista de Antropología Social, 2010)
Human rights have been much discussed in many academic, political and activist contexts in recent years. Anthropology, for long identified as critically opposed to the idea of universal human rights and the UN Charter, has recently reversed its position with a revised statement on human rights adopted by the AAA. This paper takes an innovative approach to the concept of human rights, including specifically the relevant meaning of the term “human”, which converges with, and supports, the approach taken by the new AAA statement. Like the latter, it develops the concept of negative human rights in combination with a positive ground comprising an anthropological understanding of the relevant meaning of “human” for purposes of human rights discourse and activism.
Keywords: “Human”; Human rights; Negative rights; Human difference